(untitled) (The Pakistan Development Review, 2025)
Incomplete combustion of polluting fuels (PF) is a major source of indoor pollution which poses severe risks of acute respiratory infections to women’s health such as cough, phlegm, and breathing difficulties. This article investigates the net impact of kitchen structural factors including the location of the kitchen and number of windows in the kitchen and cookstove technology on acute respiratory symptoms of rural women involved in cooking practices. A household survey was conducted to collect primary data from 250 rural households in Khyber Pakhtunkhwa province. Around 66 percent of rural households exclusively used polluted fuel for cooking which caused 4 respiratory symptoms among poor women. The results of the Poisson regression model revealed that the use of polluted energy in the enclosed kitchen was four times more responsible for respiratory symptoms than in the open kitchen; while an improved cookstove in the enclosed kitchen was three times more effective in controlling respiratory involvements . Concerted efforts are required to adopt short-term mitigation strategies such as improved stoves and efficient kitchen design.